(untitled) (Research, Society and Development, 2020)
Objective: to report the experience of an extension action aimed at stimulating the self-care of the elderly person. Methodology: This is a study of the type experience report, with descriptive approach and qualitative nature, carried out in a community center in the municipality of Belém. The activity was performed by ligands of the League of Systematization of Nursing Care (LASAE), with about 20 elderly of both sexes. The action was divided into three moments, the first occurred from the recognition of the place of activity; the second moment occurred through a round of conversation with approaches on topics related to healthy aging, self-care, sexuality among others; the third moment occurred from an individual activity, in which the elderly were divided into pairs and was applied to massage therapy, nail care for men and hairstyle and makeup for women. Results: The university extension activity allowed the approximation of academics with the community. In addition, in the second stage, there was guidance and identification of determinants and health conditions. Subsequently, the individual activity allowed a relaxing moment for the participants, addressing themes related to mental health, self-esteem and self-care. Conclusion: The performance of the extension activity made it possible to sensitize the elderly in relation to the benefits of self-care for their well-being.